From River Networks to Urban Networks: Notes on the Urban-Regional Dynamics of the Lower Rio Doce - Croce , Rômulo; Mendonça, Eneida Maria Souza (Farol, 2025)
This article seeks to understand the urban network of the Lower Rio Doce, a microregion located near the mouth of this river and currently comprised of the municipalities of Baixo Guandu, Colatina, Linhares, and Marilândia. To this end, it initially develops a historical investigation that identifies the main milestones linked to the establishment of the urban foundations of the Lower Rio Doce, in addition to listing some of the impacts of this process on the environment, territory, and local population. Finally, using secondary statistical data and the IBGE's REGIC survey, the study seeks to understand the contemporary spatial structure of this urban network. It reveals, on the one hand, its increasing complexity due to the economic dynamism of some cities, and, on the other, that this development has not translated into a more environmentally adequate and socially equitable microregional space.
Keywords: urban network; urban rivers; Rio Doce; Lower Rio Doce; urbanization